Surgical proceeding in the patient with compound odontoma of the maxilla – a case report - Gnatek, Adrian; Osica, Piotr; Janas-Naze, Anna (Journal of Education, Health and Sport, 2017)
Odontogenic tumor-like lesions are the one of the most commonly presented in jawbones. In the article described 9-year-old patient case who had been treated surgically due to compound odontoma of the left maxilla in the anterior segment. In the patient observed typical for odontogenic tumors in children persisted deciduous teeth. It results from the lack of the eruptive force of permanent teeth, blocked by the mass of the tumor. Any pathological lesions of the oral cavity in children require deep analysis and proper surgical proceeding.